Prediction Model Kualitas Aplikasi Sistem Informasi Pembayaran Tiket (E-Ticket) Yang Dipengaruhi Oleh Budaya Organisasi Serta Dampaknya Terhadap Kualitas Informasi Akuntansi Untuk Pengambilan Keputusan - Lilis Puspitawati; Novi Indriani Siti Nurshalihat (Labkat Press KA FTIK UNIKOM, 2020)
The success of the Accounting Information System in producing quality information is the culture of the organization. Accounting Information Systems play an important role in an organization for the achievement of organizational goals that are effective and efficient. The existence of an accounting information system in an organization is nothing but to be able to produce useful information for its users in the decision making process. To be able to produce quality accounting information, we need a reliable accounting information system in processing data and transactions so that the information generated can be useful in decision making. The method used in this research is descriptive and verification methods. Observation Unit conducted at PT. Kereta Api Indonesia (Persero) Bandung City with its analysis unit are employees in the accounting sub-division 20 people and the system 20 people. The statistical test used is the calculation of Structural Equation Modeling (SEM) with a variance-based analysis of Partial Least Square (PLS) and hypothesis testing using the help of the Smart PLS 3.0 application. Based on the research conducted it can be seen that (1) Organizational culture significantly influences the quality of accounting information system (2) the quality of accounting information system significantly influences the quality of accounting information.